A Collaborative Study to Establish a Standard for High Molecular Weight Urinary-Type Plasminogen Activator (HMW/u-PA) - Gaffney, P J; Heath, A B (Thrombosis and Haemostasis, 1990)
An international collaborative study involving eleven laboratories located in eight countries was undertaken to establish an International Standard for high molecular weight urinary-type plasminogen activator (HMW/u-PA). The current International Reference Preparation (IRP code numbered 66146) for urinarytype plasminogen activator (u-PA) ot urokinase (see Nomenclature footnote) is a 66/34 molar ratio mixture of low molecular weight (LMW) - and high molecular weight (HMW) - u-PA’s and is considered unsuitable as a standard for homogeneous preparations of HMW/u-PA. The putative standard for HMWu-PA (code number, 87/594) was compared for potency in a clot lysis assay with the current IRP for u-PA (code numbet, 66146) and a lyophilised preparation of single chain urinary-type plasminogen activator (SCuPA), the latter being used in the assay without prior activation by plasmin to its active two chain form (TCuPA).Both the proposed standard for HMWu-PA (871594) and the SCuPA compared in a statistically satisfactory manner in parallel line bioassays with the current IRP for u-PA (66146), thus allowing potency estimates to be obtained for these two materials in relation to defined international units. Data from the eleven laboratories indicated that each ampoule of the proposed standard for HMWu-PA contained 4,300 i. u. of activity and was stable for over 1 year at 4° C. Most participants indicated that SCuPA expressed only a small amount of its activity without a prior activator step and this suggests that SCuPA assays need to be preceded by a plasmin activation stepThe Expert Committee on Biological Standardization of the World Health Organisation (Geneva, Oct 1989) established 871 594 as the International Standard for high molecular weight two chain urinary type plasminogen activator (HMW/TCuPA, of HMWu-PA), with an assigned unitage of 4,300 international units per ampoule.